(untitled) (Castilla. Estudios de Literatura, 2020)
This article explores the identity of a rich narrative corpus that chooses Hollywood as an object of study and target for criticism to question the values of modern American society. It is obvious that many novels published throughout the 20th century have been more attracted to the vices and shortcomings of the American film industry than to its more dazzling aspects, even though they have sometimes used satire and a cynical eye to show that other side of reality. Likewise, despite the fact that most of the texts cited in this work are novels written by American authors, this dystopian fictional line proliferates in a larger map that encompasses other representative genres and subgenres, as well as literary productions of various nationalities.